2018
DOI: 10.1016/j.rmed.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychiatric disorders on the course of lung cancer, chronic obstructive pulmonary disease and tuberculosis

Abstract: To our knowledge, this is the first epidemiological study investigating the influence of a psychiatric comorbidity on the course of COPD, lung cancer and TB at a national level. Our results emphasize the importance of detecting these major respiratory diseases in patients with psychiatric comorbidities and intensifying the treatment and follow up of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
0
16
0
7
Order By: Relevance
“…The reason behind why COVID-19 disproportionally affects COPD patients is uncertain. It may be partly due to the majority of COPD patients having one or more comorbidities [4]. In addition, the chronic nature of COPD, the severity of lung function impairment, and concomitant low-grade inflammation may compromise immune mechanisms and predispose to acquiring acute respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…The reason behind why COVID-19 disproportionally affects COPD patients is uncertain. It may be partly due to the majority of COPD patients having one or more comorbidities [4]. In addition, the chronic nature of COPD, the severity of lung function impairment, and concomitant low-grade inflammation may compromise immune mechanisms and predispose to acquiring acute respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic disorder among TB patients was 29.6% in South Africa (Peltzer et al, 2013). Mental illnesses are also a cause of poor quality of life, TB treatment interruption, and poor treatment outcomes (Ambaw et al, 2018;Pachi et al, 2013;Sikjaer et al, 2018;Theron et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…WHO (World Health Organization) also ranked the COPD as the third leading cause of death in COVID 19 patients due to compromised immune response and disease progress to dyspnea, hypoxia, dry cough, excessive fatigue, and sputum production. [45][46][47][48] Lue et al 2020, concluded that COVID-19 patients with specific features like COPD, smoking and HTN, rather than cancer-specific features, are the greatest determinants of severity. 49 A large case series from many countries showed that pre-existing COPD worsens the risk of COVID-19 progression and leads to poorer prognostics.…”
Section: Discussionmentioning
confidence: 99%